Food system transformation in Mozambique: An assessment of changing diet quality in the context of a rising middle class - Smart, Jenny; Tschirley, David; Smart, Francis C. (International Food Policy Research Institute, 2018)
Robust income growth combined with the highest urban population growth in the world is driving rapid changes in the food system of Sub-Saharan Africa. Demand is increasing for higher quality foods, including fresh produce, meat and dairy products as well as more processed foods, with poorer nutritional value. The overweight and obesity epidemic that first began among developed nations is also threatening the expanding middle classes within developing countries, leading to a double burden of over and under nourished populations. As rapidly expanding towns and cities proliferate across Sub-Saharan Africa, urban areas can also become deserts for fresh or less-processed nutritious foods. Urban farming has been one way that the food desert challenge in urban areas is ameliorated, and in Mozambique, even in the largest city center of Maputo, one in ten households owns their own farm land. In the context of rapid urbanization and income growth in Mozambique, this paper finds that both growing incomes and the consumption of processed foods are associated with a worsening of negative factors in the diet. Furthermore, urbanization, controlling for income, is associated more strongly with a worsening of negative factors than with an improvement in positive factors in the diet. However, the effect on nutrition of owning one’s own farm, controlling for the share of others in the household’s area that have a farm, is positive and significant for urban households, primarily driven by these households purchasing fewer unhealthy foods. These findings have important implications concerning the role of urban farming for improving dietary quality.